2014
DOI: 10.1016/j.jamcollsurg.2013.12.064
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Pulmonary Function after Metastasectomy for Childhood Osteosarcoma: A Report from the St Jude Lifetime Cohort Study

Abstract: Background Complete resection of lung metastases improves survival in patients with osteosarcoma. We evaluated the long-term effect of metastasectomy on pulmonary function of patients treated for osteosarcoma during childhood. Methods We reviewed the medical records of patients who had pulmonary function tests (PFTs) following metastasectomy for osteosarcoma. Patient, tumor, and treatment variables were abstracted along with PFTs. PFTs were recorded as a percentage of predicted value and were classified as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“…Estimates indicate there are nearly 50,000 survivors of pediatric bone and soft tissue sarcoma in the United States; 36,723 are younger than age 50 years [3]. Because curative treatment requires a multimodal approach involving surgery, radiation, and chemotherapy, sarcoma survivors are at risk for therapy-related complications [4,5]. Medical late effects, including infertility, gonadal hormone deficiency, second malignant neoplasms, cardiomyopathy, pulmonary dysfunction and renal insufficiency have been documented [4,611].…”
Section: Introductionmentioning
confidence: 99%
“…Estimates indicate there are nearly 50,000 survivors of pediatric bone and soft tissue sarcoma in the United States; 36,723 are younger than age 50 years [3]. Because curative treatment requires a multimodal approach involving surgery, radiation, and chemotherapy, sarcoma survivors are at risk for therapy-related complications [4,5]. Medical late effects, including infertility, gonadal hormone deficiency, second malignant neoplasms, cardiomyopathy, pulmonary dysfunction and renal insufficiency have been documented [4,611].…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary dysfunction in children with scoliosis has been previously studied [6, 25]. Denbo and colleagues reported that osteosarcoma survivors who required lung resection had worse pulmonary function, but this association in survivors with scoliosis had not been previously reported [26]. The lack of association between impaired pulmonary function and performance on the six-minute walk test is unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…left in place after the patient is discharged, and then checked and removed when possible in an outpatient setting. After pulmonary metastasectomy for cancer, Pulmonary function can be impaired in patients in treatment and also in adult survivors (28,29), who often present restrictive syndrome and decreased physical function.…”
Section: Discussionmentioning
confidence: 99%